Journalism and change in time experience in Western society - Franciscato, Carlos (Brazilian journalism research, 2005)
The purpose of this paper is to investigate the temporality produced by journalistic practice and the ways journalism has a privilege to build a speciﬁ c type of social experience of the present time. This inquiry carries out a historical journey, but it is not our purpose to present a history of press in the sense of a history of institutions, particular genres and languages. Instead, this investigation develops a historical study in order to identify social temporal phenomena produced by journalism, and to express them in the form of descriptive categories, which give regularity to a diversity of temporal phenomena: instantaneity, simultaneity, periodicity, novelty, and public disclosure. Besides, we consider this work a theoretical study that uses historical elements to analyze, through a sociological approach, fundamental aspects of a social constitution of journalistic temporality.